Ab Initio Energy Calculations and Macroscopic Rate Modeling of Hydroformylation of Higher Alkenes by Rh-Based Catalyst - Shaharun, Maizatul Shima; B.K., Dutta; H., Mukhtar (Wiley Subscription Services Inc., 2009)
Ab initio quantum chemical computations have been done to determine the energetics and reaction pathways of hydroformylation of higher alkenes using a rhodium complex homogeneous catalyst. Calculation of fragments of the potential energy surfaces of the HRh(CO)(PPh3)3-catalyzed hydroformylation of 1-decene, 1-dodecene, and styrene were performed by the restricted Hartree-Fock method at the second-order MØller-Plesset (MP2) level of perturbation theory and basis set of 6-31þþG(d,p). Geometrically optimized structures of the intermediates and transition states were identified. Three generalized rate models were developed on the basis of above reaction path analysis as well as experimental findings reported in the literature. The kinetic and equilibrium parameters of the models were estimated by nonlinear least square regression of available literature data. The model based on H2-oxidative addition fitted the data best; it predicts the conversion of all the alkenes quite satisfactorily with an average deviation of 7.6% and a maximum deviation of 13%.